(untitled) (Terr@ Plural, 2022)
The world is experiencing a moment of apprehension, which began in late 2019 and extended throughout the years 2020/21 which corresponds to the pandemic period of Covid 19. The disease arrived in Brazil in late February and spread all over the country. In Ponta Grossa, it arrived a few months later and the first case of community transmission occurred on 05/26/2020. From this date on, it was possible to establish correlations between the climate and Covid 19, considering air temperature (maximum, average, and minimum) and solar radiation, the main goal of this paper. With the elaboration of graphs and statistical treatment of the data, it was possible to determine the correlation between climatic variables and the new cases of Covid 19. It should be noted that it is necessary to continue the research to better understand the moment we are living and the mentioned relationships.